Brunner’s Gland Hamartoma: A Rare Cause of Gastrointestinal Bleeding – Case Report and Review of the Literature - David R Stolpman; Gordon C Hunt; Brett Sheppard; Hahn Huang; Deepak V Gopal (Canadian Journal of Gastroenterology)
An unusual cause of upper gastrointestinal bleeding is described in a previously healthy 45-year-old man who was admitted to hospital with weakness and fatigue, and had experienced an episode of melena two days before admission. His medical and surgical history was unremarkable. Upon admission to hospital, he showed evidence of iron-deficiency anemia, with a hemoglobin concentration of 61 g/L (normal range 135 to 175 g/L), a mean corpuscular volume of 73 fL (normal range 85.0 to 95.0 fL) and a ferritin concentration of 1.0 µg/L (normal range in males 15 to 400 µg/L). Upper gastrointestinal endoscopy revealed a 3.5 cm ulcerated submucosal mass in the third portion of the duodenum, for which mucosal biopsies were nondiagnostic. A subsequent endoscopic ultrasound revealed a 2.7×4.0 cm hyperechoic, cystic, submucosal tumour in the third portion of the duodenum. Endoscopic ultrasound-guided fine needle aspiration revealed no malignant cells. The patient eventually underwent a resection of the third portion of his duodenum. Surgical pathology revealed that this tumour was a Brunner’s gland hamartoma, 4.5 cm in its greatest dimension.